THE EFFECT OF FLIPPED INSTRUCTION MODELS (FIM) ON STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXT AT SEVENTH GRADE IN SMP NEGERI 1 LADONGI - Muh. Arbianto; Dzul Fikri; Mutmainnah Mustofa; Sonny Elfiyanto (Language-Edu, 2022)
In a line with the development of technology, many teachers use flipped instruction model as their model to teach in the classroom, especially in reading class. Flipped instruction model is an inverse learning method of the traditional method in which students are usually given material by the teacher in class, and then the assignment will be done at home. Hence, this research aimed to determine the effectiveness of flipped instructions model on students’ reading comprehension of descriptive text. Quantitative research was the type of research with the Experiment method. The design is pre-experimental that utilizes one group pre-test and post-test without a control group. There were two variables in this research: independent and dependent variables, where the independent variable is flipped instruction model and the dependent variable is the students’ reading skills. The participants in this research were 33 students from SMP NEGERI 1 LANDONGI, consisting of 12 males and 21 females. The pretest was given to measure students’ prior reading skills before applying treatment. After the treatment, the students are given a test as a post-test. A total of 20 multiple-choice questions were included in the pre-test and post-test. SPSS 16.0 for Windows was used to analyze the data and hypothesis testing (paired-sample T-test). The value of sig. (2 tailed) is 0.000. The T-test is lower than 0.05 (0.000 < 0.05).According to the result, the researcher interprets that using Flipped instructions model was effective to teach reading comprehension, especially in descriptive text.